Uganda - Country Assistance Evaluation, 2001-07 - World Bank (World Bank, Washington, DC, 2012)
The World Bank (WB) and the African Development Bank (AfDB) programs in Uganda over 2001-07 were delivered under the FY01-03 the WB Country Assistance Strategy, the 2002-04 AfDB Country Strategy Paper, and the Uganda Joint Assistance Strategy. These strategies focused on promoting governance, growth, and human development, and were pursued through a net commitment of $2.1 billion by the International Development Association (FY01-07) and $732 million equivalent (2002-07) by the African Development Fund. The World Bank's assistance strategies showed strong client orientation and were aligned with Uganda's poverty reduction strategy. The programs were substantially effective in decentralization, public sector reform, growth and economic transformation, education, and water and sanitation. More could have been done to help counter the perception of increasing corruption, improve power supply, reduce transport costs, enhance agricultural productivity, and help with family planning and reproductive health. The AfDB's assistance was also relevant and aligned with the government's development goals. Its support substantially achieved its objectives for decentralization, public sector finance, growth and economic transformation, improved competitiveness, agriculture, and water and sanitation, as well as education and health. There were some shortcomings in the assistance provided for power and roads and in reducing corruption. The International Finance Corporation's (IFC's) main contribution has been in telecommunications, in addition to playing a substantial role in providing assistance for institutional and regulatory reforms in leasing and in supporting the supply response to these reforms. Limited impact was seen in small and medium enterprise (SME) access to finance, despite significant joint effort with the WB.